2018
DOI: 10.1177/1090198118769346
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Efficacy and Outcome Expectations From Child Participation in Bicycle Trains for Commuting to and From School

Abstract: A BTI improved child self-efficacy, parent self-efficacy, and parent outcome expectations, which warrants a larger RCT to examine long-term changes to these behavioral constructs and ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…After removal of 776 duplicates, 1143 articles were screened. Nine relevant studies evaluating seven unique interventions were included in this review [44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removal of 776 duplicates, 1143 articles were screened. Nine relevant studies evaluating seven unique interventions were included in this review [44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…In the section "confounders", only one study [48] did not report adjustments. The other eight studies [44][45][46][47][49][50][51][52] reported adjustments for at least two up to eight out of ten different covariates (i.e., age, distance from home to school, sex/gender, AST, BMI, race, bike score, neighbourhood disorder, attendance, accelerometer wear time). However, group differences at baseline were only absent in two studies [44,51].…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding bicycle-related equipment, previous research remained unclear on whether “the equipment of a child’s bicycle is a potential determinant of cycling to school” [ 33 ] (p. 290). Nevertheless, the only overall effective bicycle intervention in our recent systematic review [ 12 ] was conducted in the USA and provided every child with a bicycle and related equipment (i.e., helmet, lock, lights) prior to the beginning of the intervention [ 34 , 35 ]. In our study, girls rated a lock and brakes as important equipment, whereas boys rated only a lock as important equipment.…”
Section: Discussionmentioning
confidence: 99%